Bentuk Optimalisasi Teknologi Informasi dalam Mendukung E-Commerce Usaha Kecil dan Menengah - Hadi, Noor (BISNIS, 2017)
This research are intended to explore the utilization of information technology for small and medium enterprises (SMEs)to develop market share in the form of e-marketing. The results showed that SMEs in the city of Semarang has utilized information technology, from the simplest to the advanced. Hand Phone and computer are a tool that used it, although for computers not all SMEs have been using it. The form of communications media used by SMEs such as: SMS, whatshap, e-mail, website, blog, istagram, blackbarry, line, and the like. The acceptable outcomes of SMEs when they use technology are in addition to encouraging increased sales, as well as obtaining convenience when communicating with customers, ordering, marketing products, identifying customer needs, identify supplier needs, consumer surveys and the like.